PERANAN ORANG TUA MURID TERHADAP PEMBERIAN IMUNISASI LANJUTAN PADA ANAK SD LABUY KECAMATAN BAITUSSALAM ACEH BESAR - Maidayani Maidayani; Aditya Candra (Jurnal Sains Riset, 2021)
Currently, based on the 2013 Basic Health Research (Riskesdas), the complete basic immunization coverage increased from 41.6% (2007) to 59.2% (2013), but still 32.1% were immunized, while coverage Basic immunization in Aceh Province is still below the national average, which is 37.0% the reasons for never being immunized or not completing immunizations are mothers are worried about side effects, often get sick, and parents argue that immunization is haram. Knowledge of parents, especially mothers, is very important to understand the benefits of immunization for Indonesian children. The purpose of the study was to provide further information regarding the knowledge, attitudes and education of parents with the completeness of advanced immunization for elementary school children. This research is descriptive. The population and sample in this study were the number of parents of children from SD Labuy, Baitussalam District, Aceh Besar, as many as 42 people. Data analysis was carried out by descriptive statistical methods for each research variable using the distribution frequency based on the percentage of each variable. The results of the study found that the knowledge of parents of students on giving further immunizations to children was in the good category, namely 29 respondents (69.0%). Suggestions for researchers are expected to add insight, knowledge, especially in the field of medical health and for general medical education at Abulyatama University so that it can be used as reading in the library for additional literature.Keywords: Role of parents, Provision of further immunization, Children